2007
DOI: 10.1002/rcm.3189
|View full text |Cite
|
Sign up to set email alerts
|

Studies of iridoid glycosides using liquid chromatography/electrospray ionization tandem mass spectrometry

Abstract: Fragmentation pathways of five iridoid glycosides have been studied by using electrospray ionization multi-stage tandem mass spectrometry (ESI-MS(n)). The first-stage MS data of the five iridoid glycosides were compared. The MS spectra showed that the adduct ions of iridoid glycosides and the formate anion were diagnostic ions to distinguish iridoid glycosides with a carboxyl group at the C-4 position or an ester group at the C-4 position. The MS fragmentation pathways of the five iridoid glycosides were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
40
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 20 publications
9
40
0
Order By: Relevance
“…The fragmentation was followed by successive losses of H 2 O, which produced another two major peaks with m/z at 183.0664 and 165.0555. On the other hand, ring cleavages of the aglycone moieties (Ren et al, 2007) were also observed in the spectra. The product ions, such as those at m/z 157.0506 and 139.0399, were characteristic fragments produced by ring cleavage of the basic skeletons, which provided valuable information characterizing the basic structural skeleton.…”
Section: Iridoid Glycosidesmentioning
confidence: 92%
“…The fragmentation was followed by successive losses of H 2 O, which produced another two major peaks with m/z at 183.0664 and 165.0555. On the other hand, ring cleavages of the aglycone moieties (Ren et al, 2007) were also observed in the spectra. The product ions, such as those at m/z 157.0506 and 139.0399, were characteristic fragments produced by ring cleavage of the basic skeletons, which provided valuable information characterizing the basic structural skeleton.…”
Section: Iridoid Glycosidesmentioning
confidence: 92%
“…The fragmentation pathways of [M − H] − are usually applied to molecules with acid groups, such as carboxylic acids and phenols. [16,17] Recently, Levsen and coworkers [18] have applied CID to protonated and deprotonated molecules generated by ESI or atmospheric pressure chemical ionization (APCI [18] which has furnished important data for MS/MS users.…”
Section: Introductionmentioning
confidence: 99%
“…More detailed elucidation for fragmentation of iridoids in negative ion mode can be found in reference literature. 26,65 …”
Section: Identifi Cation Of Iridoids By Msmentioning
confidence: 99%